Labour Productivity Growth and Convergence in Agriculture of the European Union - GoÅ‚aÅ›, Zbigniew (International Journal of Economics and Financial Issues, 2019)
The main objective of the presented paper is to examine and assess the changes in labour productivity in the EU agriculture in the context of the diversity of its level and dynamics of change underlying the identification of labour productivity convergence/divergence processes taking place in agriculture. The labour productivity convergence processes in the EU agriculture were analysed based on data from the period between 2005 and 2016, by testing two its basic types, namely sigma and beta convergence. The analysis applied statistical measures describing the degree of labour productivity differentiation in agriculture of the EU countries and cross-sectional regression function. The research showed that sigma and beta convergence exist in general in the EU-28 countries. Keywords: labour productivity, convergence, agriculture, EU. JEL Classifications: Q13, O47, C2 DOI: https://doi.org/10.32479/ijefi.8041